REVIEW OF SAFETY AND TOLERANCE OF OMALIZUMAB - A.V. Emel'yanov ("Paediatrician" Publishers LLC, 2008)
The review of safety of monoclonal anti-ige-antibodies (xolair) - a new medication for the treatment of severe allergic bronchial asthma is presented. Local and system adverse events, originating after injection of medicament in clinical studies and following administration in patients are discussed.Key words: children, bronchial asthma, monoclonal anti Ige antibodies.